Pengaruh Substitusi Pasir Besi Morotai Sebagai Agregat Halus Terhadap Kuat Tekan, Kuat Lentur dan Penyerapan Air Batako - Elfira Resti Mulya; Anggriyawan Djafar; Fitro Darwis (Jurnal Serambi Engineering, 2024)
Iron sand, a natural resource found on Morotai Island, has not been fully exploited, unlike beach sand, which is commonly used as a building material for local bricks. However, the exploitation of beach sand may lead to beach erosion on the island. This research aims to investigate the effect of using iron sand as a partial replacement for fine aggregate in bricks on compressive strength, flexural strength and air absorption. The experimental method was carried out in the laboratory with variations in iron sand substitution ranging from 0% to 25% at 5% intervals. The results indicate that iron sand substitution can significantly affect the compressive strength, flexural strength and air absorption of the bricks. Bricks with 25% iron sand substitution showed a 75.23% increase in compressive strength, reaching 9.48 MPa. In addition, the flexural strength of bricks with 25% iron sand substitution increased by 4.66 MPa compared to bricks without substitution, an improvement of 12%. Furthermore, the air absorption test showed that the 25% iron sand substitution reduced the water absorption of the bricks by up to 25.21%. This suggests that a higher percentage of iron sand replacement in the bricks results in a lower water absorption capacity.